Targeted Disruption of Ing2 Results in Defective Spermatogenesis and Development of Soft-Tissue Sarcomas - Saito, Motonobu; Kumamoto, Kensuke; Robles, Ana I.; Horikawa, Izumi; Furusato, Bungo; Okamura, Shu; Goto, Akiteru; Yamashita, Taro; Nagashima, Makoto; Lee, Tin-Lap; Baxendale, Vanessa J.; Rennert, Owen M.; et al. (PLOS ONE, 2010)
ING2 (inhibitor of growth family, member 2) is a member of the plant homeodomain (PHD)-containing ING family of putative tumor suppressors. As part of mSin3A-HDAC corepressor complexes, ING2 binds to tri-methylated lysine 4 of histone H3 (H3K4me3) to regulate chromatin modification and gene expression. ING2 also functionally interacts with the tumor suppressor protein p53 to regulate cellular senescence, apoptosis and DNA damage response in vitro, and is thus expected to modulate carcinogenesis and aging. Here we investigate the developmental and physiological functions of Ing2 through targeted germline disruption. Consistent with its abundant expression in mouse and human testes, male mice deficient for Ing2 showed abnormal spermatogenesis and were infertile. Numbers of mature sperm and sperm motility were significantly reduced in Ing2−/− mice (∼2% of wild type, P<0.0001 and ∼10% of wild type, P<0.0001, respectively). Their testes showed degeneration of seminiferous tubules, meiotic arrest before pachytene stage with incomplete meiotic recombination, induction of p53, and enhanced apoptosis. This phenotype was only partially abrogated by concomitant loss of p53 in the germline. The arrested spermatocytes in Ing2−/− testes were characterized by lack of specific HDAC1 accumulation and deregulated chromatin acetylation. The role of Ing2 in germ cell maturation may extend to human ING2 as well. Using publicly available gene expression datasets, low expression of ING2 was found in teratozoospermic sperm (>3-fold reduction) and in testes from patients with defective spermatogenesis (>7-fold reduction in Sertoli-cell only Syndrome). This study establishes ING2 as a novel regulator of spermatogenesis functioning through both p53- and chromatin-mediated mechanisms, suggests that an HDAC1/ING2/H3K4me3-regulated, stage-specific coordination of chromatin modifications is essential to normal spermatogenesis, and provides an animal model to study idiopathic and iatrogenic infertility in men. In addition, a bona fide tumor suppressive role of Ing2 is demonstrated by increased incidence of soft-tissue sarcomas in Ing2−/− mice.